Analisis Dampak Adanya Mal Mitra Terhadap Pendapatan Pedagang Pasar Baru Kutowinangun - Setiyawan, Rahmat; Pudjianto, Hary; Barokatuminalloh, Barokatuminalloh (Lingka Ekonomika, 2022)
Modern markets or malls develop not only in big cities but also into small cities, this will have an impact on the income of merchants in traditional markets. This study aims to determine the impact of the existence of Partner Mall on the number of workers, the number of customers, and the net income of traders in the traditional market (Pasar Baru Kutowinangun). The population in this study was the traders of Pasar Baru Kutowinangun in Kutowinangun District. Sampling using simple random with a total of 52 people based on the Taro Yamane formula. The data analysis techniques used are descriptive statistics, revenue cost analysis, normality test, and Wilcoxon Signed Rank Test. Based on the results of the analysis, it was obtained that the workforce, the number of customers, and net income decreased after the existence of the Mitra Mall. The implication of this study is that there is a need to increase the competitiveness of traditional markets through increased promotion, facilitating transactions, or by changing the conditions of traditional market appearance to be more attractive.